Convolutional Neural Networks for Leaf Disease Classification - Carvalho, Raí G.; Zoby, Leticia T. M. (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2018: Anais do XV Encontro Nacional de Inteligência Artificial e ComputacionalDO - 10.5753/eniac.2018.4428, 2018)
This paper aims to improve the classification process of leaf diseases in plantations, reducing the need to have a specialist or prior knowledge of the diseases that can affect a plantation, since some diseases can spread and end with entire plantations. The proposal is the use of Convolutional Neural Networks (CNN) to classify leaf diseases in plants using images, creating a model that can be implemented in a smartphone application. The model selected for the application, using a dataset with 4485 images separated in 5 classes, had an accuracy of 97% in the test base.